Invariant set design of decentralized control for islanded microgrids under plug-and-play operation. (June 2021) - Bayoumi, Ehab; Soliman, Hisham M.; Albadi, Mohammed; Soliman, Mostafa
Highlights: An efficient decentralized control is developed. The global system is decomposed into subsystems that have local controllers installed for each subsystem. The dynamic effect of the rest of the system on a particular subsystem is formulated as an external disturbance. The proposed tracker achieves fast response with zero steady-state error and rejects the external disturbance. An LMI-based theorem is presented for the tracker's design which optimally rejects the external disturbance. A new simple invariant-sets tracker design is provided (compare with the feedforward, and weighting matrices selection in the H∞ control [2]). The proposed controller ensures the MG robust stability under plug-and-play functionality of all DGs, in addition to load changes. Abstract: This article presents a new invariant-set design for voltage regulation of islanded microgrids (MGs) composed of several distributed generators (DGs). The advantages of the proposed control are: (1) the control structure is decentralized, and (2) it tracks the reference inputs quickly and maintains robust stability against the MG's load changes and plug- and-play operation. To achieve these objectives, the global system is decomposed into several subsystems. Each DG subsystem is modeled as a linear time-invariant system with norm-bounded uncertainty representing load changes. For a specific subsystem, the effect of the rest of subsystems is represented as a disturbance. The effect of the disturbance on the subsystem is reduced by minimizing the volume of its invariant ellipsoid (approximating and bounding its invariant set). The changes in the disturbance is modeled by the norm-bounded form. The controller design is based on a derived sufficient condition in the form of nonlinear matrix inequality (solved iteratively by fixing a positive scalar as a convex linear matrix inequality, LMI, optimization problem). To evaluate the effectiveness of the proposed control strategy, different time-domain simulations are conducted using MATLAB/SimPowerSystems Toolbox. Simulations demonstrate that the suggested controller provides excellent performance in terms of voltage tracking under load changes and MG's plug-and-play operation.